Of Haunted Spaces: Cinema, Heterotopias, and China’s Hyperurbanization: Ella Raidel. With contributions by Itty Abraham, Ute Meta Bauer, Marlene Rutzendorfer, and Weiying Yu. Singapore: Nanyang Technological University Centre for Contemporary Art Singapore, 2023. 125 pp. Paperback. ISBN 978-98-11-85893-2. - Adrian Tan (Wacana Seni Journal of Arts Discourse, 2025)
This review examines Of Haunted Spaces: Cinema, Heterotopias, and China’s Hyperurbanization by Ella Raidel, a publication that bridges cinematic practice and critical urban studies. At the centre of the book is Raidel’s exploration of China’s “ghost cities”—monumental yet uninhabited urban developments that serve as both subjects and stages for her films. More than an artist monograph, the volume engages with multidisciplinary perspectives, featuring contributions from scholars such as Ute Meta Bauer, Marlene Rutzendorfer, Itty Abraham, and Yu Weiying. These texts situate Raidel’s hybrid documentary-fictional films within broader conversations on heterotopia, speculative urbanism, postcolonial theory, and architectural cinema.